Opioid-induced pancreatitis: A case study - Anuka Koul; Jaspreet Kaur; Sahil Attri; Navneet Arora (Journal of Acute Disease)
Rationale: Opioids, the class of drugs, frequently used for pain relief in acute pancreatitis are known to act as a dual-edged sword. They are capable of causing acute pancreatitis though very rare. Patient’s Concern: A 45-year-old male presented with complaints of acute onset, severe pain in the abdomen, radiating to the back. The symptoms were preceded by regular oral intake of opium. Diagnosis: Opioid-induced pancreatitis. Interventions: He was managed conservatively with non-opioid analgesic-acetaminophen 15 mg/kg every 6 hours along with intravenous Ringer’s lactate for 5 days. Outcomes: The patient was discharged in stable vitals. Lessons: Drug-induced pancreatitis, though a rare entity, must be dealt with a high degree of suspicion once the other common factors are ruled out. Thus, this case highlights the importance that opioids can act as a double-edged sword in the way that it is given for pain relief in patients suffering from pancreatitis and can also be the culprit in causing it.